2019
DOI: 10.14710/jitaa.45.1.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNP g.643G>A of MYF5 gene polymorphism with body weight and body measurements in Bali cattle

Abstract: This study aimedto identify the SNP g.643G>Aof MYF5 genethen associate it with body weight and body size measurements in Bali cattle. Blood samples were collectedfrom 80 bali cattle at BPTU-HPT Denpasar Bali. Data on phenotypic properties observed included; birth weight, live weight, average daily gain, body length, chest depth, withers height, hip height, and heart girth. Polymorphismof the MYF5 gene was identifiedusing the PCR-RFLP method. Association of MYF5 genotypes with body weight and body size measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, some did not. Association studies between MYF5 and PLAG1 with body weight and size in Bali cattle from BPTU-HPT Denpasar have shown no significant (Saputra et al 2020;Fahira et al 2022). In contrast, the previous studies reported that each genotype has a different effect on the economic feature.…”
Section: Association Of Genotype With Growth Traitsmentioning
confidence: 98%
“…However, some did not. Association studies between MYF5 and PLAG1 with body weight and size in Bali cattle from BPTU-HPT Denpasar have shown no significant (Saputra et al 2020;Fahira et al 2022). In contrast, the previous studies reported that each genotype has a different effect on the economic feature.…”
Section: Association Of Genotype With Growth Traitsmentioning
confidence: 98%
“…In pigs, MYF5 polymorphism was associated with meat quality traits (Liu at al., 2007) and in knockout mice, experiments demonstrated that the MYF5 gene affected muscle development (Lynes et al, 2015). However, the MYF5 gene with SNP g.643G>A had different results in Bali cattle in that it could not be used as a genetic marker for body weight and still needs to be evaluated in a comprehensive study (Saputra et al, 2016).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…This enzyme only hit one (1) cutting site: AATT. Saputra et al (2020) stated that restriction enzymes cut DNA fragments at specific base sequences.…”
Section: Polymorphism Of Gh Genementioning
confidence: 99%